Clinical relevance of molecular genetics to paediatric sarcomas. Issue 11 (27th April 2007) - Slater, Olga; Shipley, Janet
Abstract : The application of cytogenetic and molecular genetic analyses to paediatric sarcomas has identified a number of characteristic changes associated with types and subtypes of sarcomas. This has led to increased understanding of the underlying molecular biology of some sarcomas and provided an important adjunct to standard morphological and immunohistochemical diagnoses. Characteristic genetic abnormalities, particularly specific chromosome translocations and associated fusion genes, have diagnostic and in some cases prognostic value. There is also the potential to detect micrometastastic disease. Fusion genes are most readily detected by fluorescence in situ hybridisation and reverse transcription-PCR technologies. The expression profiles of tumours with specific fusion genes are characteristically similar and the molecular signatures of sarcomas are also proving to be of diagnostic and prognostic value. Furthermore, fusion genes and other emerging molecular events associated with sarcomas represent potential targets for novel therapeutic approaches which are desperately required to improve the outcome of children with certain categories of sarcoma, including rhabdomyosarcomas and the Ewing's family of tumours. Increased understanding of the molecular biology of sarcomas is leading towards more effective treatments which may complement or be less toxic than conventional radiotherapy and cytotoxic chemotherapy. Here we review paediatric sarcomas that have associated molecular genetic changes which can increase diagnostic and prognostic accuracy and impact on clinical management.